Analisis Dinamis Perkiraan Inflasi Indonesia : Pendekatan ARIMA Model dan Error Correction Model - Utami, Nunung Nurastuti (Akutansi Bisnis & Manajemen ( ABM ), 2006)
foresting is progress to estimate the next period value and different value Bypass and corn value is not real value but is practice for future value titik Rima autoregresif integrated Moving Average) model is one simple test of the question model if residuals estimate from the model around white noise titik di semester is not on constructing single equation of simulta news equation model but on leasing the profibilitic of stock has stick, properties Of Economic time series on there on Under The Filosofi let the data speak home the self,. Rima model art sometime call a teoretic model drive from any Economic teori ekonomi teoritis dan the basic of equation model. The best model of this riset Isma (0,0,1 mate of inflation Indonesia tahun 2005 2005) is 11,19% titik Dek aku dari of this value from one year, if the new data is come the four casting value word rejective and we can computer the value of next period titik the structure model of inflation with the long Run PPP konsep use ecm (error correction model) approach. This model can explain that the model is True or no komando komputer impact of predictor variabel to independen variabel in the short Run and long run. In the short Run Indonesia inflation and USA inflation are not signification to exchange read in the long Run, impact of Indonesian inflation to asking read is 0,173%, this Resort resep the bypotesis Indonesian inflation has positive in page to asking read and imported of USA inflation is 0,292%, the impact of USA inflation is reject the teoretical that USA inflation has negative impact to asking rate